Deradicalization Through Multicultural Islamic Religious Education at The Islamic University - Burhan Djamaluddin; Syamsul Bahri; Abdul Halim; Nurlailah; Muhammad Chabibi (Universitas Pesantren Kh abdul Chalim Mojokerto, 2024)
In the context of preventing radicalism, it is important to research educational institutions that have implemented multicultural Islamic education. This article explains how deradicalization is pursued through Multicultural Islamic Education at Universitas Islam Malang (UNISMA. This research uses a qualitative method with a phenomenological approach to understand the role of Islamic religious education in shaping students' multicultural attitudes. Data were collected through observations, interviews with 15 alumni from three cohorts, and documentation, focusing on the integration of multiculturalism concepts in the course materials. The findings indicate that the Multicultural PAI doctoral program at UNISMA significantly contributes to preventing radicalism by promoting tolerance and inclusive religious education. The program encompasses both theological and socio-cultural aspects, which help transform students' mindsets to become more open and reinforce the values of Bhinneka Tunggal Ika and Pancasila within the framework of Islamic education. The curriculum serves as a deradicalization tool by deepening the understanding of diversity and encouraging positive interactions within and between religious communities. However, its effectiveness is influenced by students' subjective factors, such as their attitudes, and external factors like the sociopolitical context. Further research is needed to assess the program's long-term impact and refine the curriculum based on student feedback.